(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article the author reviewed the features of the teaching of law – the requirement of law. In the field of education in the curriculum it occupies a special place right. In demoktraticheskom society youth aspiring to pravovovmu obrozovanie is the driving force, and its foundation is the knowledge of their rights and responsibilities. Appropriately, teaching youth legal education and instilling them the legal culture is one of the most important strategic directions. Key words: law, education, rule of law, legal culture, law.